Autonomic Abnormalities in Patients With Primary Sjogren’s Syndrome – Preliminary Results - Brunetta, Enrico; Shiffer, Dana; Mandelli, Pietro; Achenza, Sara; Folci, Marco; Zumbo, Aurora; Minonzio, Maura; Cairo, Beatrice; Jacob, Giris; Boccassini, Laura; Puttini, Piercarlo Sarzi; Porta, Alberto; et al. (Frontiers in Physiology, 2019)
Primary Sjögren's syndrome (pSS) is an autoimmune disease affecting exocrine glands and extra-glandular organs. There are conflicting reports on the presence of autonomic dysfunction in pSS and no data are available on the functional status of sympathetic outflow to the vessels and baroreceptor (BRS) control mechanisms. We investigated the cardiac (cBRS) and sympathetic (sBRS) baroreceptor modulation in both time and frequency domains and the cardiovascular autonomic profile in pSS patients compared to healthy controls. Autonomic symptoms were quantified by the COMPASS31 3-item questionnaire. The ESSPRI questionnaire evaluated the magnitude of pSS clinical symptoms, i.e. fatigue, pain and sicca symptoms. ECG, beat-by-beat arterial pressure and respiratory activity were continuously recorded in 17 pSS patients and 16 healthy controls, while supine and during 75° head-up tilt. In 7 patients and 7 controls, muscle sympathetic nerve activity (MSNA) was measured. Spectrum analysis of RR variability provided markers of cardiac vagal modulation (HFRR n.u.) and sympatho-vagal balance (LF/HF). The power of low frequency (LF,0.1Hz) oscillations of systolic arterial pressure (SAP) variability (LFSAP) evaluated the vasomotor response to sympathetic stimulation. Compared to controls, pSS patients scored higher in total COMPASS31 (p<0.0001) and all ESSPRI subdomains (fatigue, p=0.005; pain, p=0.0057; dryness, p<0.0001). Abnormal scialometry (<1.5 ml/15 min) and Shirmer tests (< 5 mm/5 min) were found in pSS patients and salivary flow rate was negatively associated with ESSPRI dryness (p=0.0014). While supine, pSS patients had lower SEQcBRS index of cardiac baroreceptor sensitivity, higher HFRR nu (p=0.021), lower LF/HF (p=0.007) and greater MSNA (p=0.038) than controls. No differences were observed in LFSAP between groups. During orthostatic challenge, although LFSAP increased similarly in both groups, MSNA was greater in pSS patients (p=0.003). At rest pSS patients showed lower cardiac baroreflex control and greater parasympathetic modulation. Furthermore, greater sympathetic nerve activity was observed in pSS patients while supine and in response to gravitational challenge. We hypothesized that such enhanced sympathetic vasoconstrictor activity might reflect an attempt to maintain blood pressure in a setting of likely reduced vascular responsiveness.